Promising method for improving the accuracy of estimates in space debris tasks - Optimal filtering of measurements. (March 2023) - Usovik, I.V.; Nazarenko, A.I.
Abstract: Space debris poses an increasing threat to functioning spacecraft, as well as people and property on Earth. Every year, dozens of large spacecraft re-entry into atmosphere and reach Earth's surface, while there is always a risk of damage to people or property. To date, several collisions have occurred in near-Earth space, which can be avoided in future if appropriate characteristics of warning systems of such events are provided. The main method of parrying threats associated with space debris is warn about dangerous situations – time and place of large objects re-entry, a possible collision between spacecraft and space debris or another spacecraft. To implement this method and solve corresponding problems, it is necessary to have updated data on parameters of space objects orbits by measurements. Improving accuracy of estimating spacecraft orbits parameters and their subsequent prediction is necessary to ensure safety of space activities in conditions of a large number of space debris. The article presents main mathematical relations of optimal filtering of measurements method, it is shown that use of this method can significantly improve results accuracy of time of re-entry and space object as collision probability estimates, in comparison with the traditionally used least squares method. The results of using optimal filtering of measurements method are shown when predicting re-entry time and place of Tiangong-1 orbital station using available open data. A posteriori evaluation of accuracy prediction results showed that use of optimal filtering of measurements allows increasing accuracy of estimates up to several times, while not increasing computational complexity. One of ways to mitigate new space debris is active removal. Currently, work on space debris active removal has moved from research to being implemented in daily practice of space activities. In coming years, a number of projects will be implemented to remove spent upper stages, rocket bodies and spacecraft from orbits. The article present results of comparing areas for space debris active removal obtained by a method that takes into account optimal filtering of measurements method with a specific list of objects obtained by a group of international experts. As can be seen from the comparison - out of 50 objects, 48 fall into calculated areas, which indicate a good correspondence of results obtained earlier with estimates of international specialists group. In this regard, it can be assumed that in order to prevent collisions that can lead to a large formation of new objects in near future, both the ranges of orbits in altitudes and inclinations, and specific objects have been determined. The use of optimal filtering of measurements method in monitoring and warning systems for hazardous events related to space debris will increase efficiency of their functioning with existing measuring instruments. Highlights: Basics of optimal filtering method. Example of optimal filtering method on Tiangong-1 re-entry. Comparison active debris removal regions and list of top objects for active debris removal.